All-metal meta-surfaces for narrowband light absorption and high performance sensing. (13th October 2016) - Liu, Zhengqi; Liu, Guiqiang; Fu, Guolan; Liu, Xiaoshan; Huang, Zhenping; Gu, Gang
Abstract: We report an experimental scheme for high performance sensing by an all-metal meta-surface (AMMS) platform. A dual-band resonant absorption spectrum with a bandwidth down to a single-digit nanometer level and an absorbance up to 89% is achieved due to the surface lattice resonances supported by the resonators array and their hybridization coupling with the particle plasmon resonances. The sensing application in the analysis of the sodium chloride solution has been demonstrated, where remarkable changes from a spectral 'dark state' to 'bright state' and vice versa are observed. Sensing performance factors of the figure of merit exceeding 50 and the spectral intensity change related FoM* up to 1075 are simultaneously achieved. The corresponding detection limit is as low as 8.849  ×  10 −6 RIU. These features make such an AMMS-based sensor a promising route for efficient bio-chemical sensing, etc.